Lead concentrations and isotope ratios in blood, breastmilk and feces: contribution of both lactation and soil/dust exposure to infants in a lead mining area, Kabwe, Zambia. (1st October 2021) - Toyomaki, Haruya; Yabe, John; Nakayama, Shouta M.M.; Yohannes, Yared B.; Muzandu, Kaampwe; Mufune, Tiza; Nakata, Hokuto; Ikenaka, Yoshinori; Kuritani, Takeshi; Nakagawa, Mitsuhiro; Choongo, Kennedy; Ishizuka, Mayumi
Abstract: Lead (Pb) poses a serious public health concern. Breastmilk may be a possible source of Pb exposure in infants, as Pb can be transferred from the maternal blood to breastmilk. The present study was undertaken to determine the Pb exposure and the contribution of lactation as one of the exposure pathways to infants in a Pb mining area, Kabwe, Zambia. Blood, breastmilk and infants' feces were collected from 418 pairs of infants and mothers. The Pb concentrations, isotope ratios in the samples, and biochemistry in mothers' plasma were analyzed. The overall mean of blood lead levels (BLLs) in infants and mothers were 18.0 and 11.3 μg/dL, respectively. High Pb concentration in breastmilk (range: 0.4–51.9, mean: 5.3 μg/L) above the WHO acceptable level between 2 and 5 μg/L were found and could be one of the sources of Pb exposure in infants. The Pb isotope ratios in infants' feces were the most similar to Pb ratios in the soil samples. The results suggest that infants are also exposed to Pb from the environment. Pb exposure in infants through breastfeeding and soil ingestion could potentially exceed daily intake of Pb which causes neurodevelopmental toxicity. In contrast to the high BLLs in mothers, the plasma biochemical profiles of most analyzed parameters were interestingly within, or close to, the standard reference values. Our data suggest that environmental remediation is urgently needed to reduce the Pb exposure in infants and mothers from the environment in Kabwe in parallel with chelation therapy. Graphical abstract: Image 1 Highlights: Blood, breastmilk and infants' feces from 418 pairs of infants and mothers were used. The highest BLLs in infants and mothers were 93.4 and 82.6 μg/dL, respectively. High Pb concentrations in breastmilk above the acceptable level (WHO) were found. Pb isotope ratios in infants' feces were similar to those in Pb contaminated soil. Infants in Kabwe could be exposed to Pb through breastfeeding and from environment.